Hello,

I have a problem where I have solved for Y and need to now solve for X. I am having trouble solving for X.

Y =(X/2) * (PX/PY)

X = (M/PX) - ((Py/PX) *Y))

Subsituting Y in to the equation gives:

X = (M/PX) - ((Py/PX) * ((X/2)*(PX/PY)))

I am having trouble working out the steps to break this down. I wrote the answer in my notes from class as:

X = (2M)/(3PX)

But I'm getting stuck on working out the steps.

Here is what I do:

Py/PX cancels out, so you are left with:

X = (M/PX) - (X/2)

Then I move X to one side:

(X/2) + X = (M/PX)

From here I can't remember what to do. I can't tell if I wrote the answer down wrong, or if I am just rusty. I am not sure how we get to:X = (2M)/(3PX)

Any help would be great. Thanks.